Minimally invasive functional approach for cholesteatoma surgery. (24th March 2014) - Hanna, Bassem M.; Kivekäs, Ilkka; Wu, Yi‐Hsuan; Guo, Lee J.; Lin, Huang; Guidi, Jessica; Poe, Dennis
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Report the efficacy of a functional minimally invasive approach for cholesteatoma surgery. Study Design Retrospective review of surgical cases performed between 1996 and 2008. Methods One hundred sixty‐nine patient charts were reviewed in which ears with primary cholesteatomas that extended beyond the mesotympanum were operated on with a plan for canal wall up (CWU) mastoidectomy. The surgical approach consisted of progressive exposure from transcanal to postauricular tympanoplasty to CWU mastoidectomy, as needed, to identify and lyse the fibrous attachments that bind the capsule to the surrounding mucosa. Endoscopic guidance was employed as appropriate to minimize exposure needs. Any planned second‐stage operations were attempted with a transcanal approach if appropriate and with endoscopic assistance. Results One hundred eighty‐four ears of 169 patients were included. The median age was 32 years (range, 1–79 years). The mean follow‐up was 3.2 years (range, 1–11 years). Eighty‐three (45%) were planned for a second‐look operation, and three (2%) required unplanned second operations. The overall recurrence rate was 24/184 (13%), and the unexpected residual rate was 5/184 (3%). The residual rate with endoscopy (5/119, 4%, ) or without endoscopy (1/65, 2%), were not significantly different. Hearing results in 156 ears improved significantly, from a preoperative pure‐tone average (PTA) of 41 dB to a postoperative PTA average of 29 dB (P < .0001). Conclusions A functional minimally invasive approach to cholesteatoma surgery provided equivalent residual rates but higher recurrence rates compared to published canal wall down mastoidectomy. Endoscopic techniques were helpful in providing adequate views while minimizing exposure. Level of Evidence 4 Laryngoscope, 124:2386–2392, 2014